La responsabilidad social empresarial como criterio orientador para la sostenibilidad y la ética de las actividades del sector bancario (2015)
This article pretends to analyze the behavior and practices of the banking sector identifying the practices that adjust in a best and a worst manner to the concept of Social Responsibility. Therefore, the focus will be on the concept of corporate social responsibility applied to the banking sector through the various existing initiatives in order to determine the current situation of the sector and to make evident the future challenges and perspectives of the sector in this field.